The Role of OTT Platforms in Storytelling: Insights from A Series of Unfortunate Events - Dumpala, Karishma; Reddy, G. Chenna (Journal of Neonatal Surgery, 2025)
This paper delves into the significance of the role of the Over-the-Top (OTT) platforms which offer a new lens to the literary works and retell in using different means like adapting into movies or T.V. series. This paper investigates A Series of Unfortunate Events by Lemony Snicket to delve into the idea further. The adaptation of Lemony Snicket’s A Series of Unfortunate Events into a Netflix original series brings an intersection of the traditional media with digital streaming platforms brings a fresh light and the engagement of the audience with such new experiments can also be an interest of further research. By comparing the film adaptation of the series which was directed by Brad Silberling which came in 2004 to that of the Netflix adaptation from 2017-19, the main focus of this paper would be to understand the revolutionary change that the OTT platforms have brought to the production of the content and thereby its reception of it. The paper also aims to address the amount of creative liberty that the OTT platforms can afford while they produce the project along with breaking down the analysis of the narrative. The adaptation by Netflix has advantage of more production values as it would have fewer constraints like the traditional broadcasts there by it can even offer a distinct visual style and the ability to address mature themes in a more nuanced way than previous iterations. This paper also throws light on how the data driven approach of the platform influences the content creation and the audience targeting, allowing for broad range of inclusivity and appealing to larger audience. Through this case study, the paper demonstrates how OTT platforms like Netflix are not only transforming the distribution and consumption of content but are also redefining the creative processes behind film and television adaptations, ultimately changing the cultural significance and global reach of literary works in the digital age.